PAPER CLAY DARI LIMBAH KERTAS BEKAS SEBAGAI UPAYA MENGATASI KETERBATASAN BAHAN PRATIKUM TANAH PATUNG - Putra Jaya, Gede (Program Studi Seni Murni ISI Bali, 2025)
The issue of environmental pollution due to household waste, office waste, agricultural waste, and livestock waste, which has become a global issue, requires a solution. One type of waste that is quite commonly found in several environmental units of the Faculty of Fine Arts and Design, ISI Bali, is used paper waste. Practical materials for the realistic sculpture course in the Fine Arts Laboratory of the Faculty of Fine Arts and Design initially used Jogja clay and plasticine as the forming materials, but over time these materials became difficult to obtain because they had to be transported from Jogja, which required a large cost to get to Denpasar. For this reason, the creation and testing of substitute materials that have almost the same characteristics or perhaps have advantages over the previous material, namely in the form of paper clay. The purpose of this research is to solve the problem of scarcity of clay practical materials and be able to overcome environmental problems, especially used paper waste in laboratories and several units within the Faculty of Fine Arts and Design ISI Bali. The creation process includes the exploration stage, the improvisation stage, and the composition stage (forming). The results of the research obtained are that clay from used paper as a practical material is very easy to obtain and produce and is much more economical when compared to sculpture soil. The characteristics of paper clay are better than sculpture soil, such as having a higher level of strength, smaller shrinkage, easier to shape and stick, and faster drying time.